2014
DOI: 10.33899/rjs.2014.86052
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aspergillus Species in Dried Fruits Collected from Duhok Market and Study their Aflatoxiginic Properties

Abstract: Samples from four types of dried fruits (apricot, fig , grapes and plum) were collected from local markets at Duhok governorate and surveyed for their contamination with Aspergillus species. A total of 20 species of Aspergillus were isolated on DRBC medium. A.awamori, A.carbonarius, A.flavus, A.fumigatus, A.japonicus, A.niger, A.ochraceus, A.parasiticus and A. tubingensis were detected from all types of dried fruits. The most frequent species was A.niger followed by A.flavus. Aflatoxigenic potentials of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Shundo et al [24] and Lewis and Schneider [25], proved that, aflatoxins B1 and G1 occurred most frequently and in high quantities in fruit and their products. [26] and Saadullah and Samir [20] proved that, A. flavus and A. parasiticus which grow on many agricultural commodities are the most significant aflatoxigenic fungi. Abyaneh et al [27] and Rodrigues et al [28] found that, A. parasiticus strains are usually strongly aflatoxigenic, producing both AFBs and AFGs.…”
Section: Determination Of Aflatoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shundo et al [24] and Lewis and Schneider [25], proved that, aflatoxins B1 and G1 occurred most frequently and in high quantities in fruit and their products. [26] and Saadullah and Samir [20] proved that, A. flavus and A. parasiticus which grow on many agricultural commodities are the most significant aflatoxigenic fungi. Abyaneh et al [27] and Rodrigues et al [28] found that, A. parasiticus strains are usually strongly aflatoxigenic, producing both AFBs and AFGs.…”
Section: Determination Of Aflatoxinsmentioning
confidence: 99%
“…Rhizopus nigricans, R. stolonifer and Penicillium spp. Saadullah and Samir [20] isolated thirty one species assigned to 14 genera from dried figs. Aspergillus was represented by 12 species and showed the widest diversity among all recorded genera, followed by Penicillium which represented by five species.…”
Section: Control Of the Toxigenic Aspergillus Parasiticus Fungusmentioning
confidence: 99%
“…A study by Asia and Samir (34) showed apricot and fig as the highest abilities to produce aflatoxin. Similarly, another study (35) found the highest concentration of AFB1 in apricot and fig (138.28 µg/kg, 46.18 µg/kg) respectively.…”
Section: Detection Of Afb1 Naturally Contaminated Nuts and Dried Frui...mentioning
confidence: 99%